2006
DOI: 10.1271/bbb.60076
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulation Effect of Jellyfish Collagen

Abstract: Certain edible large jellyfishes belonging to the order Rhizostomeae are consumed in large quantities in China and Japan. The exumbrella part of the edible jellyfish Stomolophus nomurai was cut and soaked in dilute hydrochloric acid solution (pH 3.0) for 12 h, and heated at 121 degrees C for 20 min. The immunostimulation effects of the jellyfish extract were examined. The jellyfish extract enhanced IgM production of human hybridoma HB4C5 cells 34-fold. IgM and IgG production of human peripheral blood lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 14 publications
0
25
0
2
Order By: Relevance
“…7) Hence, yellowtail heart extract may also affect translation as well as transcription activity. It is also possible that stimulated cell proliferation due to yellowtail heart extract results in accelerated IgM production, as for jellyfish collagen, 6) but this is unlikely because the cultivation period of HB4C5 cells with yellowtail heart extract was no more than 6 h in this study.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…7) Hence, yellowtail heart extract may also affect translation as well as transcription activity. It is also possible that stimulated cell proliferation due to yellowtail heart extract results in accelerated IgM production, as for jellyfish collagen, 6) but this is unlikely because the cultivation period of HB4C5 cells with yellowtail heart extract was no more than 6 h in this study.…”
Section: Resultsmentioning
confidence: 86%
“…4) Also, we have found that jellyfish extract stimulates Ig production by HB4C5 cells and Ig and cytokine production by human PBLs. 6) Because jellyfish extract treated with a collagenase lost immunostimulation activity and purified collagen from bovine Achilles' tendon accelerated IgM production of hybridoma cells, it is probable that the active substance in jellyfish extract is collagen. We examined the mode of action of jellyfish collagen and found that it stimulated not only transcription activity, but also translation activity accelerating Ig production.…”
mentioning
confidence: 99%
“…Jellyfi sh are believed to contain collagen, which moisturise the skin, and to cure rheumatoid arthritis and bronchitis (Hay 2006 ;Sugahara et al 2006 ). They provide Aequorin and Obelin, which are green fl uorescent proteins that are for instance used as biomarkers in biomedical research.…”
Section: Impacts Of Jellyfi Sh Blooms On the Provision Of Ecosystem Smentioning
confidence: 99%
“…This concept is supported by disparate lines of evidence. Whilst the nematocyst-derived venom of the edible jellyfish Nemopilema (Stomolophus) nomurai causes cardiovascular depression in experimental animals [11] and may cause death in humans [12], the collagen extracted from the exumbrella of this jellyfish enhanced IgM, IgG, interferon and tumour necrosis factor production by human lymphocytes [13, 14]. This source of collagen also enhanced inflammatory cytokine secretion, antibody secretion and population changes in immune cells [15].…”
Section: Jellyfish and Their Mechanism Of Stingingmentioning
confidence: 99%